Site-directed spin labeling studies on nucleic acid structure and dynamics - Sowa, Glenna Z. (2008)
Site-directed spin labeling (SDSL) uses electron paramagnetic resonance (EPR) spectroscopy to monitor the behavior of a stable nitroxide radical attached at specific locations within a macromolecule such as protein, DNA, or RNA. Parameters obtained from EPR measurements, such as internitroxide distances and descriptions of the rotational motion of a nitroxide, provide unique information on features near the labeling site. With recent advances in solid-phase synthesis of nucleic acids and developments in EPR methodologies, particularly pulsed EPR technologies, SDSL has been increasingly used to study the structure and dynamics of DNA and RNA at the level of the individual nucleotides. This chapter summarizes the current SDSL studies on nucleic acids, with discussions focusing on literature from the last decade.